Kohabitasi (Kumpul Kebo) dalam Perspektif Hadits Riwayat Bukhari dan Muslim serta Pasal 411 dan Pasal 412 KUHP - Rara Aura Audya; Tajul Arifin (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
This study aims to discuss the phenomenon of cohabitation (kumpul kebo) in the perspective of the Hadith Narrated by Bukhari and Muslim and its relevance in articles 411 and 412 of the Criminal Code. This study uses a descriptive analysis method with a normative legal approach through laws and regulations and the Hadith Book of Sahih al-Bukhari, and literature related to the research topic. The data collection technique uses a literature study with its analysis technique using qualitative data analysis, to understand the moral implications of adultery and to understand the sanctions for adultery in the context of cohabitation. This study also provides an understanding and education about the negative impacts of relationships without a legal marriage. The research findings show that cohabitation is considered a form of adultery that is detrimental to both parties, both from a religious and legal perspective. This study concludes by emphasizing the importance of a legal marriage relationship according to religion and the state and staying away from adultery.